Functional requirements and design of simulation cloud platform for data center - Junwen LIU; Jiaxing XUAN (Dianxin kexue)
Electric power information system is related with the safe operation of grid.To ensure the running stability of information system,comprehensive test was needed to conduct before the system is running.Considering actual needs of the power industry at present,it's necessary to establish independent environment to conduct function of in-formation system and non-functional test so as to achieve effective operation and maintenance of information system,finding loopholes and improving robustness of the system.Based on the analysis of development of cloud data center simulation platform,the research studies construction technology,which applies to the data center cloud platform and puts forward deployment implementation plan targeted to functional requirements of platform.In this way,the guid-ance role of construction was achieved on the later cloud platform.